Community as stakeholder of the corporate social responsibility programme in Malaysia: outcomes in community development - Ismail, Maimunah; Alias, Siti Noormi; Mohd Rasdi, Roziah (Emerald Publishing Limited, 2015)
Purpose: This study aims to explore the outcome of a corporate social responsibility (CSR) programme in community development from the perspective of its participants in Malaysia. It is argued that information regarding community development CSR, the providers of CSR and the outcomes of CSR on community development in Malaysia has been scant. Hence, this study examines specifically the profiles of participants of CSR programmes in community development, the profiles of selected CSR-participating corporations, the orientation of CSR responsibilities undertaken by corporations as perceived by the participants and the types of community development contribution from CSR-participating corporations. Outcomes were determined through the results of the last two objectives. Design/methodology/approach: Building on the stakeholder theory and the work of Visser’s CSR pyramid, this article explores the outcomes of CSR resulting from the participation of individuals in the community. Data were gathered from 336 respondents who were participants of CSR programmes sampled from 58 local and multinational corporations in Malaysia. Findings: The results showed that about half of the respondents were in the younger age group with a mean age of 24.40 years. The majority of the CSR-participating corporations had implemented CSR programmes from the first decade of the millennium and had their core businesses in diverse sectors. Legal responsibility was ranked the most important orientation and ethical responsibility the least important orientation. Education-related activities formed the dominant type of CSR contribution. Research limitations/implications: The study addresses a gap in the literature on Malaysian community CSR, particularly from the perspective of the community, which is one of the important stakeholders. Originality/value: This research contributes to the scarce literature on CSR in Malaysia by analysing the way business organisations in the country contribute to community development through CSR. The findings of this study should be useful to community development practitioners, CSR providers and researchers.